Marital Bond and Genealogical Anxiety – Reaffirming the Schism between Rabbinic Texts from Babylonia and the Land of Israel - Lavi-Levḳovits, Mosheh (Journal of ancient Judaism, 2020)
Societies are constituted of thick networks of intersecting constructs: genealogical anxiety is bound up with stronger patriarchal family structures. Goody and Guichard portrayed two clusters of social features - the “Occidental” (bi-lineal family model, strengthened nuclear family, solid husband-wife relationship, monogamy, loose gender separation, and a higher status of women); and the “Oriental” (patrilineal model, broader family structure, weak husband-wife relationship, tribal importance attributed to genealogy, codes of honor and shame, legitimacy of polygamy, rigid gender separation, a lower status of women, active men, and female passivity). Following these taxonomies, the article explores the relationship between genealogical anxiety and intersecting social commitments in classical and early medieval rabbinic culture: Talmudic and Midrashic stories, as well as an exegetical narrative from an unknown Midrash preserved in the Genizah. It also claims that the earlier sources are proven helpful in reaffirming the claim for a different mode of genealogical anxiety in Babylonian sources.